Streptococcus pyogenes Phospholipase A2 Induces the Expression of Adhesion Molecules on Human Umbilical Vein Endothelial Cells and Aorta of Mice - Oda, Masataka; Domon, Hisanori; Kurosawa, Mie; Isono, Toshihito; Maekawa, Tomoki; Yamaguchi, Masaya; Kawabata, Shigetada; Terao, Yutaka (Frontiers in Cellular and Infection Microbiology, 2017)
The Streptococcus pyogenes phospholipase A2 (SlaA) gene is highly conserved in the M3 serotype of group A S. pyogenes, which often involves hypervirulent clones. However, the role of SlaA in S. pyogenes pathogenesis is unclear. Herein, we report that SlaA induces the expression of intercellular adhesion molecule 1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1) via the arachidonic acid signaling cascade. Notably, recombinant SlaA induced ICAM1 and VCAM1 expression in human umbilical vein endothelial cells (HUVECs), resulting in enhanced adhesion of human monocytic leukemia (THP-1) cells. However, C134A, a variant enzyme with no enzymatic activity, did not induce such events. In addition, culture supernatants from S. pyogenes SSI-1 enhanced the adhesion of THP-1 cells to HUVECs, but culture supernatants from the ΔslaA isogenic mutant strain had limited effects. Aspirin, a cyclooxygenase 2 inhibitor, prevented the adhesion of THP-1 cells to HUVECs and did not induce ICAM1 and VCAM1 expression in HUVECs treated with SlaA. However, zileuton, a 5-lipoxygenase inhibitor, did not exhibit such effects. Furthermore, pre-administration of aspirin in mice intravenously injected with SlaA attenuated the transcriptional abundance of ICAM1 and VCAM1 in the aorta. These results suggested that SlaA from S. pyogenes stimulates the expression of adhesion molecules in vascular endothelial cells. Thus, SlaA contributes to the inflammation of vascular endothelial cells upon S. pyogenes infection.